The pedunculopontine nucleus in Parkinson's disease, progressive supranuclear palsy and Alzheimer's disease. Issue 4 (April 1988) - Jellinger, K
Abstract : Significant loss of neurons in the pedunculopontine nucleus pars compacta (PPNc), a putative cholinergic nucleus involved in modulating somatic motor activities, has been demonstrated in progressive supranuclear palsy (PSP) and Parkinson's disease but not in Alzheimer's disease. A morphometric study of this nucleus was performed in two cases of PSP and in a cohort of cases of Parkinson's disease, Alzheimer's disease, senile dementia of Alzheimer type (SDAT), and age-matched controls. In PSP a significant 60% neuronal loss in PPNc was associated with neurofibrillary tangles in 40 to 64% of the remaining neurons. In Parkinson's disease there was a significant decrease in cell numbers and density by 53 and 51%, respectively, with Lewy bodies involving 6 to 39% of all neurons. In Alzheimer's disease and SDAT, large neurons were reduced by 29 and 33.8%, respectively, with tangles in 9 to 38% of the remaining cells. The selective affection of this putative cholinergic nucleus in PSP and Parkinson's disease appears to be related to motor dysfunctions in these disorders.